Strategic Management of International Curriculum in Arabic Language Education at Al-Ma’tuq Islamic Boarding School: Manajemen Strategis Kurikulum Internasional dalam Pendidikan Bahasa Arab di Pondok Pesantren Al-Ma’tuq - Filando , Ghazy Ahmad; miftahuddin, Ahmadmiftahuddin; Kuswardono, Singgih Kuswardono (Universitas Negeri Semarang, 2025)
This study is motivated by the importance of developing an international curriculum for Arabic language learning, especially in pesantren (Islamic boarding schools) that generally only use the National Curriculum. Amidst the tide of globalization and the need for foreign language proficiency, Pesantren Al-Ma'tuq Sukabumi is one example of a pesantren that has adopted an international curriculum for Arabic language lessons, in collaboration with the Islamic University of Madinah. This is a new development that is still rarely discussed in academic circles, as international curricula are generally only associated with English or the Cambridge curriculum. This study aims to analyze the management of international curricula in Arabic language learning at the Madrasah Aliyah level at the Al-Ma'tuq Sukabumi Islamic boarding school. The main focus of the research is to determine how the planning, implementation, and evaluation of the international curriculum applied at the Madrasah Aliyah level at the Al-Ma'tuq Sukabumi Islamic Boarding School are carried out. This research uses a descriptive qualitative approach and employs interviews, observations, documentation, and questionnaires with the head of the curriculum department, the head of the research and development, Arabic language teachers, and senior high school students to collect data. The results of the study show that: (1) The planning of the international curriculum is carried out systematically through collaboration with the Islamic University of Madinah, the development of a syllabus based on Middle Eastern standards and external oversight. (2) The implementation of the curriculum reflects an integrative approach between theory and practice, with support from an active Arabic-speaking environment and the use of official textbooks from international partner institutions. (3) The evaluation of the international curriculum is conducted in stages, with regular supervision by supervisors from the Islamic University of Madinah.